1986
DOI: 10.1246/bcsj.59.3791
|View full text |Cite
|
Sign up to set email alerts
|

The Microwave Spectrum and Molecular Structure of Methyl Selenocyanate

Abstract: The microwave spectra of CH380SeCN, CH378SeCN, CH380Se13CN, CH380SeC15N, sym-CH2D80SeCN, and asym-CH2D80SeCN have been observed. In order to determine the rotational constants of 13CH380SeCN, we used the transition frequencies observed by Landsberg. From these spectra the complete rs coordinates of seven atoms have been calculated using Kraitchman’s equation. The structural parameters (bond lengths in Å(1Å=0.1 nm) and angles in degree) are: r(C1–H1)=1.073(4), r(C1–H2)=1.083(6), r(C1–Se)=1.954(7), r(Se–C2)=1.83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…The same bond lengths in the transition state of 1 during rotation are 1.332 and 1.911 Å, respectively. The calculated geometrical parameters of 4 are in good agreement with the microwave spectroscopical results of CH 3 SeCN (CSe: 1.954 Å, SeC: 1.836 Å, CN: 1.162 Å, C‐Se‐C: 96°) and ethene (CC: 1.332) 8e. The pseudohalogeno group is linear and strongly bent at the selenium (the C‐Se‐C bond for both conformers is around 96° or 98° depending on the method).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The same bond lengths in the transition state of 1 during rotation are 1.332 and 1.911 Å, respectively. The calculated geometrical parameters of 4 are in good agreement with the microwave spectroscopical results of CH 3 SeCN (CSe: 1.954 Å, SeC: 1.836 Å, CN: 1.162 Å, C‐Se‐C: 96°) and ethene (CC: 1.332) 8e. The pseudohalogeno group is linear and strongly bent at the selenium (the C‐Se‐C bond for both conformers is around 96° or 98° depending on the method).…”
Section: Resultssupporting
confidence: 77%
“…Microwave spectroscopic studies have shown that alkyl cyanates, thiocyanates, and selenocyanates have a bent frame 8. These compounds are very rigid; the barrier to linearity is high9 and the observed C‐X‐C (X=O, S, Se) angles are 113°, 99° and 96°, respectively 8a,c,e. Alkyl isocyanates, isothiocyanates, and isoselenocyanates, on the other hand, are much more flexible than their isomeric counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison with the substitution structure of H 3 CSeCN is warranted. The Se−CH 3 bond length, which is 194.4(7) pm in this compound, is about 3 pm shorter than the Se−CH 2 bond length obtained in MP2 calculations and as much as 6 pm shorter than the B3LYP procedure predicts.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies of the structural and conformational properties of organic selenocyanates (X−Se-CN) in the gaseous state have been performed. Several years ago, the microwave (MW) spectra of methyl (CH 3 SeCN) , and ethyl selenocyanate (CH 3 CH 2 SeCN) were investigated. The structure, dipole moment, and barrier to internal rotation of the methyl group were determined for CH 3 SeCN, , whereas the conformational properties of CH 3 CH 2 SeCN were the theme of the other MW study .…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies of the structural and conformational properties of organic selenocyanates (X-Se-CRN) in the gaseous state have been performed. In one such study, the structure, dipole moment and barrier to internal rotation of the methyl group of methyl selenocyanate (CH 3 SeCN) were investigated by Sakaizumi et al 1,2 employing microwave (MW) spectroscopy. The conformational properties of ethyl selenocyanate (CH 3 CH 2 SeCN) was the theme of another MW study.…”
Section: Introductionmentioning
confidence: 99%